Da terra para as águas : trajetória de José Augusto dos Santos – (1929-2006) - Santos, Ivoneide (2019)
Writing on the history of a life consists in a difficult task, on the other hand stimulated the desire to narrate and understand the trajectory of a character excluded with little reading, black, descendant of black father, white mother, native of Sergipe and belonging to candomblé . Thus, this research aims to construct the biography of this common man by name José Augusto dos Santos, (1929-2006) in the light of the biographical genre, through the understanding of the researchers mentioned in the theoretical reference, like Dosse (2015) that evaluated the aspiration of some historians to look at the history of anonymous people in history. Therefore, this research is divided into three moments. In the first chapter we discuss the classifications built around the biographical genre: his changes, permanences and relationship with History. In the second chapter we look at the trajectory of José Augusto dos Santos, known for Zé D’ Obakossô, his involvement with candomblé in Aracaju / SE, Duque de Caxias/RJ and São Cristóvão/SE. And, finally, we describe about the public visibility, testimonies of children of the saint, participation in cultural event and awards, homage In memoriam of José Augusto dos Santos. In order to achieve this research, we consulted the following documents: newspapers, magazines of the time with materials favoring José Augusto, records of minutes, passport, drafts of a book that he had prepared, a book written by the biographer, marriage certificate, exemption from military service, photos, CDs recorded by the relatives with the songs in the area of candomblé written by José Augusto, death certificate and transfer.